ChemInform Abstract: Copper‐Catalyzed Preparation of 2‐Aryl‐3‐cyanobenzofurans with Bright Blue Photoluminescence. Issue 27 (16th June 2016) - Zhang, Lianpeng; Peng, Zhixing; Wen, Qiaodong; Li, Xihui; Lu, Ping; Wang, Yanguang
Abstract: The cascade synthesis of arylcyanobenzofurans from o‐hydroxybenzaldehydes and arylacetonitriles includes Knoevenagel condensation, cyanide anion transfer, intramolecular nucleophilic addition, and aromatization.